Experimental characterization and constitutive modeling of polyurethanes for structural applications, accounting for damage, hysteresis, loading rate and long term effects. (1st November 2019) - Nikoukalam, M.T.; Sideris, P.
Abstract: Polymers are highly customizable materials that present high potential for applications in the development of damage-resistant structural systems. Out of the various polymeric materials, polyurethanes combining high strength (2–3 times that of normal concrete) with high deformation capacity (~0.04 strain at yielding) have been recently considered in the development of damage resistant bridge columns. However, development of structural systems incorporating polyurethanes requires fundamental understanding of their mechanical properties under various loading conditions, as well as development of versatile constitutive models describing such responses. Compared to conventional structural materials, the response properties of polyurethanes include hysteresis, damage (softening), and rate dependence (viscosity) in the elastic and inelastic range. To address this challenge, this study: (i) conducts an experimental program to characterize the mechanical behavior of an amorphous thermoset polyurethane which has been (and is currently being) considered in structural applications, (ii) develops a softening viscoelastic viscoplastic uniaxial material model to simulate the observed response under various loading conditions, and (iii) develops a heuristic systematic procedure to estimate model parameters from test data. The loading conditions of the experimental program include: (a) monotonic/cyclic compression-only and tension-only loading at strain rates up to 0.1/s, (b) multi-step strain-controlled monotonic loading including constant deformation segments to quantify relaxation and capture the so-called equilibrium path, (c) cyclic combined tension-compression uniaxial loading, and (d) relaxation and creep compressive tests. The test results showed nonlinear rate dependence, asymmetric response in tension and compression, monotonic/cyclic damage, and hysteresis.